2012
DOI: 10.1515/jpem-2011-0473
|View full text |Cite
|
Sign up to set email alerts
|

A case of Rabson-Mendenhall syndrome with a novel mutation in the tyrosine kinase domain of the insulin receptor gene complicated by medullary sponge kidney

Abstract: Rabson-Mendenhall syndrome (RMS) is a genetic disorder characterized by severe insulin resistance and somatic characteristics. Recombinant insulin-like growth factor 1 (r-IGF-1) is used to treat RMS, as the IGF-1 and insulin receptors share homology. However, the effect of r-IGF-1 varies in patients and it is diffi cult to manage metabolic status appropriately in r-IGF-1 resistant cases. We report a Japanese boy with RMS who showed resistance to r-IGF-1 therapy and a novel mutation in the insulin receptor in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…Abe et al reported a case of a Japanese boy with RMS and radiological finding of MSK and nephrocalcinosis, with yet unknown aetiology to link these conditions [7]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abe et al reported a case of a Japanese boy with RMS and radiological finding of MSK and nephrocalcinosis, with yet unknown aetiology to link these conditions [7]. …”
Section: Discussionmentioning
confidence: 99%
“…Two cases have been published of associated Medullary Sponge Kidney (MSK) [6,7]. Uncertainty remains as to whether these are independent of, or characteristic features, of RMS.…”
Section: Introductionmentioning
confidence: 99%
“…Two more confounding factors were hirsutism, a common finding of RMS, 4-6 which was caused by the administration of progesterone, and the Bartter-like phenotype described in patients with syndromes of severe insulin resistance such as RMS and Donohue syndrome. 5,8,9 The latter was maybe the outcome of long-term factitious furosemide dispensation that can result in hypercalciuria, hypokalemia, and metabolic alkalosis after prolonged treatment. Finally, the infective episodes observed in our case (a common cause of death in patients with RMS and Donohue syndrome is infection) have to be attributed to the intravenous injections by the mother deliberately performed without antiseptic care.…”
Section: Figurementioning
confidence: 99%
“…Patients with impaired INSR function provide a unique opportunity to study the role of this receptor in human kidney. So far, only case reports and small case series exist in the literature, reporting an association with medullary sponge kidney [ 12 , 13 ], and a Bartter-like phenotype [ 14 ]. In order to get a better understanding, we performed a medical note review of the renal features of INSR dysfunction in the largest series of patients reported so far.…”
Section: Introductionmentioning
confidence: 99%